Vitamin D and cardiovascular disease. (September 2018) - Apostolakis, Michail; Armeni, Eleni; Bakas, Panagiotis; Lambrinoudaki, Irene
Highlights: Vitamin D is involved in cardiovascular physiology. Vitamin D deficiency is associated with increased subclinical and overt cardiovascular disease. It is still unclear whether vitamin D supplementation has a beneficial effect on cardiovascular outcomes. Patient characteristics, vitamin D status, dose/mode/duration of supplementation modulate the effect of vitamin D on CVD. Abstract: Vitamin D, a soluble steroid hormone synthesized in the skin after sun exposure, plays a crucial role in calcium metabolism and is also involved in cardiovascular pathophysiology. The aim of this review is to summarize the available evidence (a) on the association between endogenous vitamin D status and cardiovascular disease, and (b) on the effect of vitamin D supplementation on cardiovascular outcomes. Most studies have shown an inverse association between vitamin D levels and cardiovascular outcomes. Randomized controlled trials, however, do not consistently support a beneficial effect of vitamin D administration on cardiovascular health. Population characteristics, comorbid conditions such as diabetes, the overall population prevalence of cardiovascular disease, vitamin D status and the regimen of vitamin D supplementation may account for the conflicting results.